(untitled) (Nigerian Journal of Technology, 2021)
Evapotranspiration (ET) may account for up to 70% of the annual precipitation even in humid region. Understanding ET is essential for management of water resource, crop water requirement as well as irrigation designs/scheduling etc. Therefore, this study tries to analyze potential ET over Enugu State using meteorological data from weather stations and compared the results obtained with that from satellite remote sensed techniques. The meteorological data from 1999 to 2014 were collected from Nigerian Meteorological agency (NIMET) for two stations in Enugu State (Enugu town and Nsukka). The data were processed and ET calculated using CROPWAT software. Also, necessary data for ET were downloaded from global atmospheric reanalysis product by European Centre for Medium-Range Weather Forecast (ERA-Interim) and National Aeronautics and Space Administration (NASA). Daily and monthly potential ET results were estimated for Enugu and Nsukka. The potential ET obtained for both stations varies with month and seasons with higher values in dry season than rainy season. The potential ET obtained from NIMET, NASA and ERA-Interim have similar trend but varied in magnitude. Statistically, ETNIMET was the most accurate followed by ETNASA.